Dysphemism in The Comment Section of The Instagram Account @jokowi - Kurniawan, Alfauzy Riski; Markhamah, M (Universitas Muhammadiyah Surakarta, 2025)
This study focuses on the use of dysphemism in the comment section of the Instagram account @jokowi as a form of netizens' response to political and social issues in digital spaces. The aim of this research is to describe the evaluative meanings of dysphemism that appear in the comments and to explain the findings as learning materials for Indonesian language instruction at the senior high school level. The study employs a qualitative descriptive method with a digital ethnographic approach by collecting data from comments containing dysphemistic elements. The analysis reveals three categories of evaluative meanings of dysphemism: cursing (17 instances), criticizing (9 instances), and mocking (2 instances), with cursing being the dominant form through the use of harsh expressions as an indicator of public dissatisfaction toward public figures. The research findings are implemented as Indonesian language teaching materials in senior high schools to promote linguistic awareness that is polite, ethical, and responsible in digital media. The implementation is carried out through learning activities based on text analysis and critical discussion, enabling students to identify and transform dysphemistic utterances into more polite and constructive language.